กระบวนการสร้างความเป็นผู้สอนงานของช่างในโรงงานอุตสาหกรรมประกอบรถยนต์ - วงษ์สิงห์ อุดม; ปัดไธสง สุรวุฒิ; สันคติประภา กิตติกร; เจือไทย จิตติมา (บรรณศาสตร์ มศว, 2018)
บทความการวิจัยนี้มีวัตถุประสงค์เพื่อทำความเข้าใจกระบวนการสร้างตัวตนของผู้สอนงานช่างในโรงงานอุตสาหกรรมประกอบรถยนต์ ผ่านการกระทำบทบาทของการเป็นผู้สอนงาน ใช้วิธีดำเนินการวิจัยในรูปแบบของการวิจัยเชิงคุณภาพภายใต้วิธีวิทยาการสร้างทฤษฎีฐานราก ประยุกต์เข้ากับแนวคิดปฏิสังสรรค์สัญลักษณ์ผ่านการกระทำบทบาทของบุคคล โดยเก็บข้อมูลด้วยการสนทนาเชิงลึกกับช่างผู้สอนงานและนำมาตีความเพื่อวิเคราะห์ข้อมูล ผลการวิจัยพบว่า ในโรงงานอุตสาหกรรมประกอบรถยนต์เป็นพื้นที่การเรียนรู้ของผู้ปฏิบัติงานที่เอื้อต่อการสร้างตัวตนความเป็นผู้สอนงานและการใช้ความรู้เชิงประสบการณ์มาถ่ายทอดอย่างมีกระบวนการ ตั้งแต่เริ่มปฏิบัติการเข้าสู่โรงงานอุตสาหกรรม จุดเปลี่ยนสู่การสวมบทบาทของการเป็นผู้สอนงาน และตัวตนความเป็นผู้สอนงานของช่างผ่านการกระทำบทบาทจากการเรียนรู้เชิงประสบการณ์ จนเป็นผู้ที่มีความสามารถในการสอนงานให้ผู้อื่นเข้าใจและปฏิบัติได้ จึงเป็นการเปิดมุมมองให้สังคมได้เห็นและเข้าใจตัวตนความเป็นผู้สอนงานของช่างในโรงงานอุตสาหกรรมประกอบรถยนต์ ผู้ซึ่งทำหน้าที่ถ่ายทอดความรู้เชิงประสบการณ์จากการปฏิบัติว่ามีความหมายต่อคนอีกกลุ่มหนึ่งในสังคมไม่ต่างกับผู้ทำหน้าที่สอนหรือถ่ายทอดวิชาความรู้ในสถาบันการศึกษา This research aimed to understand the process of creating self – instructor as supervisor by workers in the automotive assembly plant, through the roles of the instructor under experiential learning. This was a qualitative study employing the grounded theory and applying it to the concept of symbolic interactionism, through the action of personal roles. Data were collected through an in-depth interview. According to the results, it was evident that an automotive assembly plant is a place where workers can learn and gain experience, with consistent interactions and various elements. Accordingly, the career path encompasses the processes of creating a self, in combination with a constant experiential learning, which is similar to the transfer of knowledge and professional experience between an instructor - workers and students. Hence, this reveals society a new perspective to realize and understand the nature of instructors in the automotive assembly plant, who have the responsibility to convey practical knowledge which is meaningful to certain groups in the society. In addition, these instructor - workers duty are not different from those who transfer academic knowledge in educational institutions.